Vocal outcomes after video assisted cold knife endolaryngeal phonosurgery of benign vocal fold lesions - Mishra, Sanjeev; Ullal, Aishwarya; Rathaur, Shiv Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: This study focuses on therapeutic possibilities in managing benign superficial vocal fold lesions with video assisted cold knife endolaryngeal phonosurgery. Methods: Fifty patients with benign vocal fold lesions presented to us between September 2013 and October 2015 who failed conservative therapy were subjected to video assisted cold knife endolaryngeal phonosurgery. The pre and postoperative results were evaluated based on voice rating by visual analogue scale and GRBAS scale. Results: Encouraging results were achieved with cold knife endolaryngeal surgery as 96.3% of patients were symptom free without any recurrence after single operation. Most of them have achieved >90% of voice outcome by 1 month postoperatively based on voice assessment and laryngoscopic evaluation. Conclusions: Using a telescope with high definition video system for performing phonosurgery is economic, enables the surgeon to acquire static images and video sequences. Cold knife endoscopic laryngeal surgery is possibly a better option for addressing BVFLs.